Concepciones, escenarios, tensiones y rupturas en la experiencia como maestra artista en formación de Camila Alarcón en la Licenciatura en educación artística con Énfasis en danza y teatro en 2019-2 y 2020-1 (2021)
This research monograph consists of carrying out a descriptive analysis of my experience as a Master Artist in Training from the information collected in a specific period of time that shows the process involved in the theoretical-practical subjects within the Bachelor of Arts with an Emphasis on Dance and Theater